Knowledge of Primary Education university students about first aid for dental fracture and avulsion - Salcedo Bolívar, Gabriela Tazziana (2024)
Objectives: To identify the knowledge about the immediate management of dental fracture and avulsion of Primary Education students of a national university in 2023. Materials and Methods: It was a descriptive and cross-sectional study, with a sample of 112 students that were divided into two groups, middle-year students (61) and final-year students (51), who were sent a validated virtual optional questionnaire multiple that accepts a single answer, consists of 5 general data questions and 10 knowledge questions. According to the stanine scale, it was classified into three categories: Poor (0-7.1), Regular (7.2-12.9) and Good (13-20). Results: 65.1% were women and 34.9% were men. 71.4% of the participants responded that they did not have information about first aid in dental trauma. 39.3% of the students had fair knowledge while 34.8% had poor knowledge and 25.9% had good knowledge. Conclusions: The knowledge of Primary Education students was regular.